2009
DOI: 10.1007/s00203-009-0458-y
|View full text |Cite
|
Sign up to set email alerts
|

A new Tunisian strain of Bacillus thuringiensis kurstaki having high insecticidal activity and δ-endotoxin yield

Abstract: BLB1 is a new Bacillus thuringiensis kurstaki strain, isolated from a Tunisian soil sample. Assay of toxicity of BLB1 crystal proteins resulted in an LC50 of 70.32 ng of toxin per mg of flour against third instar Ephestia kuehniella with confidence limits of (31.6-109.04 ng). This LC50 is less than that of the commercial strains HD1 used as a reference. The characterization of this strain by scanning transmission electron microscopy, analysis of its cry genes content by PCR-sequencing, and analysis of its delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
3
22
1
Order By: Relevance
“…Also, the toxin yield was calculated as 16.03 mg/10 5 spores mL ¡1 . Similar results were obtained in a study carried out by Yilmaz et al [7] Also, Saadaoui et al [27] estimated the d-endotoxin production of Btk HD1 as 669 mg mL ¡1 for 10 10 spore L ¡1 .…”
Section: Discussionsupporting
confidence: 85%
“…Also, the toxin yield was calculated as 16.03 mg/10 5 spores mL ¡1 . Similar results were obtained in a study carried out by Yilmaz et al [7] Also, Saadaoui et al [27] estimated the d-endotoxin production of Btk HD1 as 669 mg mL ¡1 for 10 10 spore L ¡1 .…”
Section: Discussionsupporting
confidence: 85%
“…The high toxicity of SUFT01 may be associated with the cry gene copy number and could be a factor in δ-endotoxin overproduction. Other studies also demonstrated that the Bt isolates with greater cry1A gene copy numbers produced more δ-endotoxin than did the reference strain HD1 (SAADAOUI et al, 2009).…”
Section: Cfus and δ-Endotoxin Productionmentioning
confidence: 92%
“…This strain produces a bipyramidal parasporal crystal exhibiting, against larvae of E. kuehniella, a higher insecticidal activity than that of the reference strain HD1 (B. thuringiensis kurstaki) [16]. The strain HD1CryB, an acrystalliferous strain, was used to produce the Cry1Ac protein of BLB1 and HD1.…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%
“…kurstaki strain isolated from a Tunisian soil sample [16]. It showed a d-endotoxin production and an insecticidal activity better than those of commercialized strain HD1.…”
Section: Introductionmentioning
confidence: 98%